A thorough performance assessment of solar chimney power plants: Case study for Manzanares - Erdem Cuce; Pinar Mert Cuce; Harun Sen (Cleaner Engineering and Technology, 2020)
Solar chimney power plants (SCPPs) are promising systems for clean energy generation. SCPPs are ideal for the large-scale harnessing of solar energy. They operate efficiently without auxiliary energy and do not cause any environmental pollution. There are several theoretical, numerical and experimental attempts to date for performance assessment of SCPPs, however, there are still contradictions in the findings, and a thorough performance evaluation is still missing. Therefore, in this study, a novel three-dimensional axisymmetric computational fluid dynamics (CFD) approach is proposed by considering the pioneer plant in Manzanares region. For a realistic approach, actual geometric parameters of the pilot plant are utilised in the CFD model, and the performance assessments are done regardless of time. Pressure, temperature and velocity distributions within the SCPP from collector inlet to chimney outlet are numerically modelled with respect to changes in solar radiation and atmospheric temperature. For model validation, the numerical findings are compared with the typical experimental findings performed in pilot plant, and a good agreement is obtained. For a certain value of solar radiation (1000 ​W/m2), maximum air velocity in the pilot plant is found to be 14.24 ​m/s, which is compatible with the experimental data of 15.00 ​m/s. Static pressure is found to sharply decrease from chimney ground to turbine inlet, and then steadily rises to the chimney outlet. Minimum static pressure is observed to be −100.18 ​Pa ​at 21.92 ​m from the ground. Output power of SCPP linearly increases with the solar intensity whereas it steadily reduces with ambient temperature. Available power is determined to be 49059 ​W for the case of 1000 ​W/m2, and the atmospheric temperature of 293 ​K.